Leksikografi og terminologi – to sider af samme sag? - Jacobsen, Jógvan í Lon (Nordiske Studier i Leksikografi, 2014)
This article deals with the borderline between lexicography and terminology. Traditionally lexicography and terminology are viewed as two separate language disciplines. But in Faroese language policy the terminology is regarded as an integrated part of Faroese language planning. One of the main objective of this article is to draw attention to the reasons why these two disciplines have better conditions to be regarded as one in the Faroes than it has in other language communities (except from the one of Iceland).